The natural history of carpal tunnel syndrome: A study of 20 hands evaluated 4 to 9 years after initial diagnosis - Resende, Luiz Antonio de Lima [UNESP]; Tahara, A. [UNESP]; Fonseca, Ronaldo Guimarães [UNESP]; Sardenberg, Trajano [UNESP] (My University, 2003)
Carpal tunnel syndrome (CTS) is the most frequent entrapment neuropathy. In the last decade several papers have been published on epidemiology, clinical aspects, diagnosis, and treatment, but little is known about its natural history. The objective of this work was to study the natural history of CTS syndrome. From 358 patients with clinical and conduction study diagnosis of CTS, 12 cases were identified that had refused surgical treatment, had not used anti-inflammatory medications, and had not undergone orthopaedic procedures, such as immobilization or anaesthetic infiltration. These 12 patients have 20 compromised hands which have been followed up for between 4 and 9 years. In all cases sensory and motor conduction studies were performed on the median nerve, at the beginning and end of follow-up period. Electrical improvement was marked in 5 hands and slight in 3; there was no significant change in 10, and deterioration in 2. As 8 hands (7 patients) showed improved clinical symptoms and conduction studies over several years, this brings the universally accepted procedure of surgical treatment into doubt.
Keywords: Carpal tunnel syndrome; Natural history; adult; aged; carpal tunnel syndrome; clinical article; controlled study; deterioration; disease course; female; follow up; human; male; median nerve; motor nerve conduction; patient attitude; sensory nerve conduction; symptom; Adult; Aged; Carpal Tunnel Syndrome; Disease Progression; Electromyography; Female; Follow-Up Studies; Humans; Male; Middle Aged; Neural Conduction; Remission, Spontaneous; Severity of Illness Index; Time Factors